Synthesis of gamma-WO3 thin films by hot wire-CVD and investigation of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit; Waykar, Ravindra; Jadhavar, Ashok; Date, Abhijit; Late, Dattatray; Pathan, Habib; Gosavi, Suresh; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2017)
In this study, monoclinic tungsten oxide (gamma-WO3) have been grown in a single step using HW-CVD method by resistively heating W filaments in a constant O-2 pressure. The formation of gamma-WO3 was confirmed using low angle-XRD and Raman spectroscopy analysis. Low angle-XRD analysis revealed that as-deposited WO3 film are highly crystalline and the crystallites have preferred orientation along the (002) direction. HRTEM analysis and SAED pattern also show the highly crystalline nature of WO3 with d spacing of similar to 0.38 nm, having an orientation along the (002) direction. Surface topography investigated by SEM analysis shows the formation of a uniform and homogeneous cauliflower like morphology throughout the substrate surface without flaws and cracks. A humidity sensing device incorporating WO3 is also fabricated, which shows a maximum humidity sensitivity factor of similar to 3954% along with a response time of similar to 14 s and a recovery time of similar to 25 s. The obtained results demonstrate that it is possible to synthesize WO3 in a single step by HW-CVD method and to fabricate a humidity sensor by using it. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim